2014
DOI: 10.5539/sar.v3n3p28
|View full text |Cite
|
Sign up to set email alerts
|

Conservation Agriculture in Zambia: Effects on Selected Soil Properties and Biological Nitrogen Fixation in Soya Beans (Glycine max (L.) Merr)

Abstract: <p>Conservation agriculture has been promoted in Zambia as a strategy to mitigate some of the negative effects arising from conventional tillage practices. Conservation agriculture offers several potential benefits on soil properties. However, these benefits and impacts vary across agro ecological regions and management practices. This study investigated changes, over time, associated with the practice of conservation agriculture in selected soil chemical, physical and biological properties, including an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…The CA benefits include less fuel consumption (Baker et al, 2007;Tahir et al, 2008;Lithourgidis et al, 2009;Akbarnia and Farhani, 2014), reduced soil loss due to enhanced aggregate stability and the protective effect of crop residues left over the soil (Friedrich et al, 2011;Sanderson et al, 2013;Vanlauwe et al, 2014). It is more productive as compared to conventional tillage because it improves soil quality and water use efficiency of plants (Samarajeewa et al, 2006;Brunel et al, 2013;Muchabi et al, 2014). Conservation tillage creates more continuous pore systems and reduces the soil porosity for aeration but increase the capillary porosity, helps improving soil water holding capacity (Bhattachariya et al, 2008;Kishor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The CA benefits include less fuel consumption (Baker et al, 2007;Tahir et al, 2008;Lithourgidis et al, 2009;Akbarnia and Farhani, 2014), reduced soil loss due to enhanced aggregate stability and the protective effect of crop residues left over the soil (Friedrich et al, 2011;Sanderson et al, 2013;Vanlauwe et al, 2014). It is more productive as compared to conventional tillage because it improves soil quality and water use efficiency of plants (Samarajeewa et al, 2006;Brunel et al, 2013;Muchabi et al, 2014). Conservation tillage creates more continuous pore systems and reduces the soil porosity for aeration but increase the capillary porosity, helps improving soil water holding capacity (Bhattachariya et al, 2008;Kishor et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Cropping sequence did not influence soil microbial biomass or activity. Earlier findings have shown that significant changes in soil microbial biomass in soils under CA are apparent only after 16 years of practice (Muchabi et al, 2014); this suggests that the length of time of practice in this case being only six years might have been too short to elicit observable changes.…”
Section: Discussionmentioning
confidence: 86%
“…Length of time under CA practice is also an essential factor determining SOC accumulation over time (Blanco-Canqui & Lal, 2007). Studies by Umar et al (2011) and Muchabi et al (2014) in Lusaka, Eastern, Southern and Central provinces of Zambia suggested that five years of CA practice would not be long enough for the effects to be significant but waiting for seven years would result in sufficient SOC accumulation. That this soil had been under CA practice for only six years could explain why SOC levels were still low and, in some cases, not significantly higher than under conventional farming.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations